(untitled) (Sustainability in Debate, 2025)
This study aimed to analyse Brazilian adolescents’ dietary environmental sustainability indicators and their associations with socioeconomic factors and nutritional status. This is a cross-sectional study using data from Brazilian adolescents (11-19 years old) from the 2015 National Students’ Health Survey. Estimates were made of the environmental footprints of adolescents’ diets, including water, ecological, and carbon footprints. Secondary variables were socioeconomic and nutritional status. Correspondence analyses were used to estimate the associative models between the secondary variables and the quintiles of each environmental footprint. The means of the carbon, water, and ecological footprints for the Brazilian adolescents’ diet were, respectively, 1206 gCO2 eq/kg (95%CI: 1192-1219), 2760 liters/kg (95%CI: 2730-2789), and 8.07 g-m2/kg (95%CI: 7.99-8.16). The lowest quintiles of the environmental footprints of food analysed were associated with dietary patterns characterised by a higher presence of ultra-processed foods and living in more urbanised areas.